Gastric emptying and duodenal motility upon intake of a liquid meal with monosodium glutamate in healthy subjects - Teramoto, Hidemi (Wiley Periodicals, Inc., 2014)
Glutamate is thought to serve as a special signal for gut functions. We investigated the effects of monosodium l‐glutamate (MSG) on gastric emptying and duodenal motility. Ten healthy male volunteers underwent rapid magnetic resonance imaging (MRI) of the abdomen. Coronal images were successively acquired after ingestion of liquid meal (200 kcal in 200 mL: 9 g protein, 28.4 g carbohydrate, 5.6 g fat, 370 mg Na(+)) with and without 0.5% MSG. During the acquisition of MRI, participants breathed freely. In all participants, the gastric residual volume gradually decreased to 80.1 ± 14.2% without MSG and to 75.9 ± 14.3% with MSG after 60 min (P = 0.45 between the groups, n = 10). In two of 10 participants, gastric emptying slowed down significantly, whereas in the remaining eight participants, gastric residual volume decreased to 84.0 ± 13.1% without MSG, and to 73.0 ± 14.6% with MSG after 60 min (P = 0.015, n = 8). There was no difference in the shape of the stomach between groups. In four of the eight participants responding positively to MSG, the duodenum wall was sufficiently identified to quantify the motions. The inclusion of MSG enhanced duodenal motility, judging from changes in (1) the magnitude of the duodenal area, (2) the center of gravity, and (3) the mean velocity of the wall motions. The third parameter most significantly indicated the excitatory effect of l‐glutamate on duodenum motility (~ three‐ to sevenfold increase during 60 min, P < 0.05, n = 4). These results suggest that MSG accelerates gastric emptying by facilitating duodenal motility, at least in subjects with positive responses to MSG.